An investigation on the mechanism of the increased NO2 emissions from H2-diesel dual fuel engine. (15th February 2018) - Li, Hailin; Liu, Shiyu; Liew, Chetmun; Li, Yu; Wayne, Scott; Clark, Nigel
Abstract: The addition of hydrogen (H2 ) into the intake air of a diesel engine was found to significantly increase the emissions of nitrogen dioxide (NO2 ). Previous research demonstrated a strong correlation between the emissions of NO2 and unburned H2 in exhaust gas. However, the mechanism whereby H2 addition in increasing NO2 formation in a H2 -diesel dual fuel engine. Previously has not been investigated. This research numerically verified the hypothesis that the increased NO2 emissions observed with the addition of H2 was formed through the conversion from NO to NO2 during the post combustion oxidation process of the unburned H2 when mixed with the hot NO-containing combustion products. A variable volume single zone model with detailed chemistry was applied to simulate post-combustion oxidation process of the unburned H2 and its effect on NO2 emissions. The mixing of the unburned H2 with the NO-containing hot combustion products was found to convert NO to NO2 . Such a conversion is promoted by the hydroperoxyl (HO2 ) radical formed during the oxidation process of the H2 . The factors affecting the NO2 formation and its destruction include the concentration of NO, H2, O2, and the temperature of the bulk mixture. When H2 and hot NO-containing combustion products mixed during the early stage of expansion stroke, the NO2 formed during H2 oxidation was later dissociated to NO after the complete consumption of H2 . The complete combustion of H2 exhausted the source of HO2 necessary for the conversion from NO to NO2 . The mixing of H2 with combustion products during the last part of the expansion stroke was not able to convert NO to NO2 since the temperature was too low for H2 to oxidize and to provide the HO2 needed. The bulk mixture temperature range suitable for meaningful conversion from NO to NO2 aided by HO2 produced during the oxidation of H2 was examined and presented. Highlights: Adding H2 to diesel engine significantly increases NO2 emissions. The increased NO2 is converted from NO with the presence of HO2 . The HO2 is produced during H2 oxidation process. There presents unburned H2 after main combustion process of dual fuel engine. The early and late boundary for unburned H2 to affect NO2 formation is developed.